2019
DOI: 10.1002/mnfr.201900553
|View full text |Cite
|
Sign up to set email alerts
|

Pru p 3‐Glycodendropeptides Based on Mannoses Promote Changes in the Immunological Properties of Dendritic and T‐Cells from LTP‐Allergic Patients

Abstract: Scope Glycodendropeptides (GDPs) functionalized with mannose can enhance allergen interaction with dendritic cells (DCs) via C‐type lectin receptors (CLRs), modulating the immune response. They can present multiple peptides and have potential applications for diagnosis and treatment of food allergy (FA). The immune response induced by GDPs with mannose and Pru p 3 peptides (mono/tetravalent) with ester (D1ManPrup3/D4ManPrup3) or ether linkers (D1Man‐O‐Prup3/D4Man‐O‐Prup3) in lipid‐transfer‐protein‐allergic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Moreover, these structures are specifically recognized by LTP‐allergic patients and have the ability to interact with DCs via CLRs, inducing their maturation and promoting the allergen‐specific proliferative response. Additionally, the monomeric compounds that were unable to bridging sIgE on basophil surface do not activate the effector response and produce higher tolerant effects 69 . These promising results indicate that glycodendrimers can be considered as promising adjuvants to be applied in allergy.…”
Section: Added Value Of Nanotechnology For Therapeutic Approaches In ...mentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, these structures are specifically recognized by LTP‐allergic patients and have the ability to interact with DCs via CLRs, inducing their maturation and promoting the allergen‐specific proliferative response. Additionally, the monomeric compounds that were unable to bridging sIgE on basophil surface do not activate the effector response and produce higher tolerant effects 69 . These promising results indicate that glycodendrimers can be considered as promising adjuvants to be applied in allergy.…”
Section: Added Value Of Nanotechnology For Therapeutic Approaches In ...mentioning
confidence: 98%
“…Additionally, the monomeric compounds that were unable to bridging sIgE on basophil surface do not activate the effector response and produce higher tolerant effects. 69 These promising results indicate that glycodendrimers can be considered as promising adjuvants to be applied in allergy.…”
Section: Use Of Nanotechnology For Treating Allergic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the lower concentration used for the glycosylated nanostructures with Pru p 3 peptides induced a tolerance response, while the higher concentration induced desensitization to peach [ 109 ]. In addition, these Pru p 3 peptide glycosystems promoted changes in the properties of DCs and T Cells and did not activate the basophils from peach allergic patients [ 110 ].…”
Section: New Therapeutic Approachesmentioning
confidence: 99%
“…Multiple studies have demonstrated that these cells are key players in immunomodulation during AIT 9 promoting tolerance, being involved in allergen transport to submandibular lymph nodes, inducing Tregs and reducing allergy symptoms 10 . Our group have demonstrated that the beneficial effects induced by SLIT with Pru p 3 can be orchestrated by DCs, by decreasing costimulatory molecules and migration markers and promoting PD-L1 expression, which is involved in the regulatory response 6 , 11 .…”
Section: Introductionmentioning
confidence: 99%